Vasha znakomaia - Kuleshov, Lev (Soviet Union, 1927)
The fragment is a part of a Soviet short silent drama film set in Moscow, during the years of the New Economic Policy. Journalist falls in love with a responsible officer at an industrial plant. This infatuation has a negative impact on her work and she got fired. Meanwhile officer's wife returns. This situation reveals the true nature of the lover who is an egoist.
Only the fragment of the film survived.
There is a possibility of choice between the subtitles in English, French, or German.